PLC Greenhouse Automatic Temperature Control Using Fuzzy Logic Method to Optimize Pakcoy Growth - harliman, saleh; Rosyad, Wafatikhur; Sutrisno, Imam; Endrasmono, Joko (STMIK Dharma Wacana, 2022)
Vegetables are a good food, especially to meet the needs of vitamins and dietary fiber. However, in urban areas, there is very little land to develop vegetable farming. Hydroponic vertical planting system can be a solution. Pakcoy plants have growth that only takes 40 to 45 days to reach the ideal harvest age. The use of a greenhouse is also suitable for better pest control. However, the greenhouse has the characteristic of storing heat that it absorbs up to 5 degrees Celsius hotter than the outside temperature. The use of greenhouses with temperature control can accelerate the growth of vegetables. Based on this problem, making temperature regulation very necessary, the way is to adjust the rotation speed of the cooling fan using the fuzzy logic method so that the main goal is to save energy and air with a lower temperature can be flowed. The use of this hydroponic greenhouse module is proven to be able to maintain the temperature not much higher than the outside temperature. Comparison of fuzzy logic output values using Matlab software and fuzzy logic output values using PLC has an average error value of 0.27% for fan 1 and 0.35% for fan 2. The performance of the fuzzy logic method used can also be said to be good with an average response time of 61.8 seconds. With the performance of the system, the environment of the greenhouse can be suitable for the plant to grow optimally.Â